Business plan for a hospitality digital content distribution service - Jíra, Pavel (2020)
The aim of this thesis is to explore a business plan for a video streaming service aimed at hospitality customers. The theoretical part reviews available literature on writing business plans and selects methods applicable for use in this business case. The practical part of the thesis sets the vision for the startup in the contemporary market context and explores the external environment of the proposed startup, estimating its perspective competitive position, necessary capabilities, and key concerns for achieving profitability.